The War on Glyphosate Spreads. (1st April 2019) - Sfiligoj, Eric
The author considers the increasing pressure that is being put on the herbicide glyphosate internationally and addresses the science and the poor recommendations that are being made by pesticide regulators. Although it has been in use in crop fields since 1974, the debate over the safety and continued use of glyphosate has never been more intense than right now. And the scope of these attacks is definitely spreading. In reality, says Bob Reiter, Global Head of Research and Development, Crop Science Division for Bayer, glyphosate should not be coming under such fire from regulators around the world. He notes that glyphosate is one of the most studied molecules that has ever been introduced into the agricultural marketplace, and time and time again, it has been shown to have a tremendous safety record. This fact, however, has been disputed in some parts of the world recently. In fact, in 2015, the World Health Organization's International Agency for Research on Cancer (IARC) published a report concluding that glyphosate was "probably a cause of cancer." Although this finding has been contradicted by research from other regulatory agencies around the world in the intervening years, many glyphosate opponents have consistently cited the IARC report as "proof" that the herbicide is dangerous to human health and should be banned.